Antimicrobial and analgesic activity of leaf extracts of Phyllanthus reticulatus Poir. (Family- Euphorbiaceae) - Haque, Tahmina; Muhsin, Mohammad Didare Alam; Akhter, Taslima; Haq, Md Emdadul; Begum, Rayhana; Chowdhury, Sk. Feroz Uddin Ahmed (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 5(1): 81-85, 2016 (June)